A utilização da criptografia no ensino de matrizes - FERREIRA, Sávio dos Reis (2022)
The present work proposes a methodological alternative to the teaching of matrices based on the use of cryptography, enabling a differentiated approach from those commonly applied in the classroom. From the processes of codification and decoding of messages, we sought to provide a more significant learning of matrices to third-year high school students from the public school system in the municipality of Belém/PA. With a qualitative approach, the research used an evaluative questionnaire of the mathematical workshop developed in the school. The results show that the application of encryption helps in understanding the basic concepts of matrices in a dynamic and interesting way.